HOW TO USE WARM UP ACTIVITIES IN THE DEVELOPMENT OF STUDENTS’ SPEAKING COMPETENCIES IN ENGLISH LESSONS - Dilrabo Mamatova, Dilrabo Mamatova (Журнал иностранных языков и лингвистики, 2021)
This article deals with how to use different types of warm up activities in the development of students’ speaking competences in the English lessons and compared ideas.